2001
DOI: 10.1002/ajmg.1570
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of chromosome 15 in epilepsy

Abstract: A number of observations point to chromosome 15 as a good candidate to harbor genes involved in epilepsy. This hypothesis is supported by at least two lines of evidence: one is the finding that haploinsufficiency of the 15q11-q13 region, of maternal origin, is responsible for Angelman syndrome, one of the cardinal manifestations of which is epilepsy; the second is the observation that extra copies of this same genomic region, in the form of inv-dup(15) or intrachromosomal duplications, again of maternal origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…This seizure rate is similar to that reported in the autistic spectrum population in general, 37 and much lower than seizure rates reported in those with idic(15). 6,8,31,32 This, however, may be artificially inflated by response bias, since parents of children with seizures may be more likely to respond to a seizure survey than parents of children with no seizures. It is also possible that families of children with more severe epilepsy might have been more likely to respond.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This seizure rate is similar to that reported in the autistic spectrum population in general, 37 and much lower than seizure rates reported in those with idic(15). 6,8,31,32 This, however, may be artificially inflated by response bias, since parents of children with seizures may be more likely to respond to a seizure survey than parents of children with no seizures. It is also possible that families of children with more severe epilepsy might have been more likely to respond.…”
Section: Discussionmentioning
confidence: 99%
“…4 Maternal duplications of this region are the most commonly identified genetic cause of autism, 5 with prevalence estimates in autism ranging from 0.5% to 3%. 3 Multiple genes from this region are implicated in the pathogenesis of autism spectrum disorders, epilepsy, and schizophrenia, 2,[6][7][8] and numerous studies implicate UBE3A as the causative gene resulting in impaired cognitive function in AS. 9 These results suggest that altered function of UBE3A through underexpression (AS) or overexpression (idic (15) or int dup (15)) impairs neurocognitive development.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…104,133,170 On the other hand, epilepsy is a well-characterized feature of Angelman syndrome 79 and is also associated with other chromosome 15q11-q13 defects, including interstitial duplications of maternal origin within the imprinted region. 46,205,208,233 A recent study of children referred from general pediatrics and neurology clinics reported a history of febrile seizures in 18 of 40 individuals (45%) with PWS and deletion, as compared with 1 of 14 patients (7%) with maternal uniparental disomy. 219 The same group reported seizures in 42 of 47 patients (89%) with Angelman syndrome and deletion, as compared with 4 of 9 patients (44%) with paternal uniparental disomy.…”
Section: Epilepsymentioning
confidence: 99%